Introduction to General Relativity, Black Holes and Cosmology - Choquet-Bruhat, Yvonne (Oxford University Press, 2023)
This book presents basic General Relativity and provides a basis for understanding and using the fundamental theory. General Relativity is a beautiful geometric theory, simple in its mathematical formulation. It leads to numerous consequences with striking physical interpretations: gravitational waves, black holes, cosmological models, and so on. The first part of the book outlines the fundamentals of the subject. Chapters in this part look at Riemannian and Lorentzian geometry, Special and General Relativity, the Einstein equations, the Schwarzschild spacetime, black holes, and cosmology. The second part presents a number of more advanced topics such as general Einstein spacetimes, the Cauchy problem, relativistic fluids, and Relativistic Kinetic Theory.